THE INFLUENCE OF SOCIO-ECONOMICS ON POLITICAL AWARENESS IN THE EFFORT TO INCREASE A NATION’S RESILIENCE (CASE STUDIES OF FIVE MAJOR CITIES IN INDONESIA) - Malini, Helma (Jurnal Pertahanan dan Bela Negara, 2023)
The existence of an income gap in political participation is explained in this article using Stylized Facts. This study examines the relationship between income and political consciousness in five major Indonesian cities using population, Growth Domestic Product (GDP), health spending, and education spending. The population effects GDP and the proportion of income allocated to Education and Health. In five main cities in Indonesia, income inequality will affect political consciousness. The population affects GDP, which in turn affects the proportion of income allocated to Education and Health. An acceptable allocation of wealth to Education and Health affects political awareness since it influences an individual’s aptitude and capacity to reason about their political perceptions.